2021
DOI: 10.1186/s13287-020-02119-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of Ndel1 during the differentiation of neural stem cells induced by hippocampal exosomesticle

Abstract: Background In the brain of adult mammals, neural stem cells persist in the subventricular zone of the lateral ventricle and the subgranular zone of the dentate gyrus, which are specialized niches with proliferative capacity. Most neural stem cells are in a quiescent state, but in response to extrinsic stimuli, they can exit from quiescence and become reactivated to produce new neurons, so neural stem cells are considered to be a potential source for cell replacement therapy of many nervous syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…N2a cells were cultured in Dulbecco Modified Eagle Medium and Ham F12 (DMEM/F12, Corning) supplemented with 10% FBS (Gibco) and 100 U/mL penicillin-streptomycin (HyClone) at 37°C with 5% CO 2 . The culture and differentiation of hippocampal NSCs were performed as described previously with some modifications [ 24 , 25 ]. Firstly, the hippocampi were derived from the brains of neonatal (1 day) ICR mice and mechanically dissociated in DMEM/F12.…”
Section: Methodsmentioning
confidence: 99%
“…N2a cells were cultured in Dulbecco Modified Eagle Medium and Ham F12 (DMEM/F12, Corning) supplemented with 10% FBS (Gibco) and 100 U/mL penicillin-streptomycin (HyClone) at 37°C with 5% CO 2 . The culture and differentiation of hippocampal NSCs were performed as described previously with some modifications [ 24 , 25 ]. Firstly, the hippocampi were derived from the brains of neonatal (1 day) ICR mice and mechanically dissociated in DMEM/F12.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to anti-inflammation and pro-angiogenesis, exosomes can also activate neural stem cells and induce differentiation into neurons. Li et al (2021) found that hippocampal niche exosomes can promote the differentiation of neural stem cells into neurons, and further studies showed that miR-3,559-3P and miR-6,324 in hippocampal niche exosomes have a pro-NSC differentiation effect ( Cheng et al, 2021 ). Not only as small molecules used in tissue engineering for SCI treatment, exosomes can also be used as carriers to load siRNA, miRNA and antagonists and deliver them to the site of injury through the “homing” function of exosomes, so that the hydrogel can play a better therapeutic role ( Huang et al, 2020 ).…”
Section: Application Of Hydrogels In Sci Repairmentioning
confidence: 99%
“…[ 229 ] Hippocampal‐derived exosomes cocultured with NSCs in vitro could promote their differentiation into mature neurons by targeting the nudE neurodevelopment protein 1 like (Ndel1) protein. [ 230 ] In addition, exosomes from human embryonic kidney 293 cell line (HEK293T) cells have been shown to efficiently achieve improved neuronal plasticity, by encapsulating circular RNA sex comb on midleg homolog‐1 (SCMH1), and recovery of neuronal functions in rodents and nonhuman primate ischemic stroke models ( Figure ). [ 137 ] Nerve fibers, formed by axons and oligodendrocytes, in the white matter of the brain are damaged in both cerebrovascular diseases and neurodegenerative diseases, which is an important cause of cognitive sequelae.…”
Section: Bnv‐based Advanced Nanotechnology For Drug Delivery For Brai...mentioning
confidence: 99%
“…siSNCA, curcumin, BAP core PD (immune inhibition) [85] Disordered protein clearing Erythrocyte membrane Cu x O nanozyme, pentapeptide KLVFF AD [226] Red blood cell membrane Curcumin, T807 molecules, PLGA core AD [227] Exosomes from bone-marrow-derived imDC siSNCA, curcumin, BAP core PD [85] Anti-neuroinflammation Exosomes from whole blood mAb GAP43, quercetin Ischemic stroke [228] Membranes of MSCs with CXCL12 high expression PDA core, A151 Ischemic stroke [159] Neuroregeneration Ginseng-derived exosomes -Neural cells [229] Hippocampal exosomes -Neural stem cells [230] EVs from HEK93T cells circSCMH1 Ischemic stroke [137] Exosomes from neural stem cells PDGFR𝛼 ligand, Bryostatin-1 Demyelinating disease [231] Angiogenesis regulation Exosomes from human MSCs MicroRNA-29a-3p Glioma (angiogenesis inhibition) [232] NVs from MSCs Iron oxide nanoparticles Ischemic stroke (angiogenesis enhancing) [47] Exosomes from MSCs -PD (angiogenesis enhancing) [233] Exosomes from MSCs Hydrogels TBI (angiogenesis enhancing) [234] Gut-brain axis regulation Exosomes from IECs -Sepsis-associated encephalopathy [235] Garlic-derived exosomes -Obesity-related brain inflammation [236] Previous studies have shown that the synthesized NIR-II responsive nanoparticles camouflaged by a tumor cell membrane and assisted by the PD-L1 small molecule inhibitor JQ1 (bromodomain inhibitor), successfully activated CD8 + T cells and decreased the number of Treg cells in the glioma immune microenvironment; [224] increased expression of immune cellular chemokines can also promote the T cell killing effect for gliomas.…”
Section: Immune Regulationmentioning
confidence: 99%